The Indonesian Ulema Council's contribution in developing Islamic religious education for the Asahan Regency community - Adnan, Adnan Syah Sitorus; Zulfiana Herni (Paedagogia: Jurnal Pendidikan, 2023)
ABSTRACT Islamic religious education is a beacon for the muslim community Received :who is being overwhelmed by darkness about their religion and leads them to become a muslim society that is in accordance with the theachings of Islam. However, this has not yet become a reality because there are still many muslim communities who have not received islamic religious education, therefor the MUI has a very important role in providing islamic religious education for the community. This study aims to find out how the roles, programs and obstacles felt by the Asahan Regency MUI in an effort to improve Islamic religious education for people in Asahan district. This study uses qualitative research with descriptive analysis methods with the stages of data collection, data reduction, data display dan drawing conclusions then described in writing. The data collection techniques used in this study were observation, interviews, literature studies and Focus Group Discussions. This research focused on : what is the role of the MUI in improving islamic religious education for the people in Asahan district; what is MUI’s program in improving islamic religious education for people in Asahan district and what are MUI’s obstacles in improving islamic religious education for people in Asahan district. The results of this study indicate that MUI has a very important role in improving Islamic religious education for the people Asahan district trough programs implemented such as regeneration of preachers, routine mitings, routine studies, and deployment of koran teachers to remote areas.